Pressure ulcers: modern approaches of prevention and treatment - N. O. Somov (Лечащий Врач, 2023)
Background. Despite the fact that in most cases the appearance of pressure ulcers can be prevented, this problem continues to be relevant, affecting up to 30 million patients in the general population. Pressure ulcers are a serious medical, social and economic problem, having a significant impact not only on the general well-being of the patient, but also on the quality of his life on the physical, emotional and psychological levels. At the same time, this disease requires serious financial costs for the treatment of one patient. Pressure ulcer (lat. decubitus) is a local damage to the skin and underlying tissues, which can be caused by prolonged exposure to continuous pressure on the tissues. The most significant risk factors for the formation of pressure ulcers include old age, cognitive impairment, limited motor activity of patients, as well as comorbid conditions, such as urinary and fecal incontinence, edema, microcirculation disorders, hypoalbuminemia, malnutrition and lack of proper care. The syndrome of prolonged compression with the subsequent development of microcirculatory disorders plays a key role in the development of pressure ulcers. Pressure ulcers are formed in places of greatest compression, where there is practically no subcutaneous fat in the area of bone or cartilaginous protrusions. Usually pressure ulcers occur on the surface of the skin above the sacrum and coccyx, the spinous processes of the spine, the calcaneus, the areas of the elbow and knee joints, the acromial process and the spine of the scapula. High-quality and regular patient care, which can be carried out both at home and in a hospital, is the best prevention of the development of pressure ulcers. In addition to care, an important role is played by medical supervision, which allows you to stop both the further progression of pressure ulcers and the development of complications.Results. Approaches of the prevention and treatment of pressure ulcers are considered, a clinical case is given.Conclusion. Treatment of pressure ulcers is a complex and time-consuming task that requires significant economic and human resources, an integrated interdisciplinary approach. The basic principle of the treatment of pressure ulcers is the adequacy of the selected treatment, based on the stage of the pressure ulcer process. In this regard, it remains relevant not only to search for new, effective methods of treating this pathology, but also to optimize the work of middle and junior care staff, as well as the active introduction of an integrated, interdisciplinary approach in the prevention and treatment of pressure ulcers.